Advances and development trends in eco-friendly pavements - Sha, Aimin; Liu, Zhuangzhuang; Jiang, Wei; Qi, Lin; Hu, Liqun; Jiao, Wenxiu; Barbieri, Diego Maria (Journal of Road Engineering, 2021)
The major contemporary in road pavement engineering is related to the creation of green and sustainable infrastructures, e.g., reduction of environmental impacts, increase in traffic safety, and transportation efficiency, etc. This review presents the recent trends in research and the technical solutions developed so far to address these challenges. After the analysis of research status in the past decades, a novel technology system of eco-friendly pavements is proposed considering two solutions, materials modification and structure improvement. The construction of an eco-friendly pavement can be achieved thanks to several different technologies ensuring permeable, noise-reducing, self-luminous, and exhaust-decomposing properties as well as apporting lower heat absorbing and enhanced anti-/de-icing characteristics. A systematic review of these technologies is presented pivoting on four main aspects: technical principle, material and structural composition, performance evaluation, and engineering application. The current trend in road engineering is combining the pavement infrastructure with various eco-friendly functions, e.g., water permeability, noise reduction, low heat absorption, exhaust gas decomposition, and anti-/de-icing. Finally, the review lists the drawbacks of the existing technologies, including high cost, single function, etc., and depicts the future developing direction and architecture of the next generation of eco-friendly pavements in which the road infrastructure should have more environmentally friendly functions than the existing technology.